From Lab to Pharmacy Shelves: The Story of a Plant Derived Anticancer Drug, "Paclitaxel" - Maira Junjua (Journal of Bioresource Management, 2015)
Paclitaxel (Taxol®) is a highly praised anticancer drug, known for its efficiency in treating different cancers. It belongs to a class of compounds called taxanes that are derived from the plants of the genus Taxus. This drug is now FDA approved, but there was a time when the name Taxol was less known to the scientific world. Taxol, being a unique molecule in its structure, properties and mechanism of action, has undergone more than 30 years of trials, and faced a lot of hurdles to leave the bench of a laboratory and reach the shelves of a pharmacy. This review focuses on the story of Taxol, how it began and how it achieved the status of Paclitaxel.